Regional and Seasonal Differences in Species Composition and Trophic Groups for Tidepool Fishes of a Western Pacific Island – Taiwan - Colin K. C. Wen; Li-Shu Chen; Kwang-Tsao Shao (Marine Science Department Diponegoro University, 2018)
Spatial and temporal variations in the species composition of assemblages are common in many marine organisms, including fishes. Variations in the fish species composition of subtidal coral reefs have been well documented, however much less is known about such differences for intertidal fish assemblages. This is surprising, given that intertidal fishes are more vulnerable to terrestrial human disturbances. It is critical to evaluate the ecology and biology of intertidal fishes before they are severely impacted by coastal development, especially in developing countries such as those in the tropical western Pacific region where coastal development is rapidly increasing. In this study, we investigated the species composition, abundance, biomass and species number (richness) for intertidal fish assemblages in subtropical (northern) and tropical (southern) Taiwan across four seasons by collecting fishes from tidepools using clove oil. We also examined the gut contents of collected fishes to identify their trophic functional groups in order to investigate regional and seasonal variations for different trophic groups. We found significant differences in the species composition of tidepool fish assemblages between subtropical and tropical Taiwan. Bathygobius fuscus, Abudefduf vaigiensis and Istiblennius dussumieri were dominant species in subtropical Taiwan, whereas Bathygobius coalitus, Abudefduf septemfasciatus and Istiblennius lineatus were dominant in tropical Taiwan. Other species such as Bathygobius cocosensis, Abudefduf sordidus and Istiblennius edentulus were common in both regions. For trophic groups, omnivores and detritivores had or showed trends towards higher species numbers and abundances in the subtropical region, whereas herbivores, planktivores and general carnivores had or showed trends towards higher species numbers and biomass in the tropical region. Overall, many intertidal fish species and trophic groups showed differences in abundance, biomass and species number between subtropical and tropical Taiwan. Further studies on large scale geographical gradients in trophic groups and species compositions in the Indo-west Pacific region are encouraged to assist with ecosystem monitoring and assessment. Keywords: Intertidal fishes, spatio-temporal pattern, feeding guild, diet